Diffuse alveolar hemorrhage due to metastatic angiosarcoma of the lung: A case report - PAN, ZHIJIE; AN, ZHOU; LI, YANYUAN; ZHOU, JIANYING (Oncology letters, 2015)
Angiosarcoma is a rare, heterogeneous malignant tumor that derives from endothelial cells, and it has aggressive characteristics with a marked tendency for distant metastasis. Diffuse alveolar hemorrhage (DAH) is a catastrophic clinical syndrome, however, it is rare as the presentation of pulmonary angiosarcoma. To increase awareness with regard to angiosarcoma and DAH, the current study presents a case of angiosarcoma that originated from the subcutaneous soft tissue of the mastoid process, but was subject to a delayed diagnosis and rapid invasion into the brain and lung. The metastatic angiosarcoma of the lung presented with DAH as the initial manifestation. The pathological examination of a biopsy of the subcutaneous mass and pulmonary lesions confirmed the diagnosis of angiosarcoma. The patient succumbed to respiratory failure at 1 month post-diagnosis.